2000
DOI: 10.1161/01.str.31.8.1925
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Emergency Medical Services for Acute Stroke in a Nonurban Population

Abstract: Background and Purpose-Activating emergency medical services (EMS) is the most important factor in reducing delay times to hospital arrival for stroke patients. Determining who calls 911 for stroke would allow more efficient targeting of public health initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
94
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 17 publications
8
94
5
Order By: Relevance
“…20 The patient was rarely the caller (2% of all calls), consistent with other series 12,20,41 and phase 2 of our research (reported earlier).…”
supporting
confidence: 90%
“…20 The patient was rarely the caller (2% of all calls), consistent with other series 12,20,41 and phase 2 of our research (reported earlier).…”
supporting
confidence: 90%
“…Prehospital delay might also occur because patients not activate emergency medical service but rather directly access emergency department, contact first a family member or the family doctor [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been estimated that only 38 to 65% of all stroke patients arrive to the hospital via the EMS system (Wein et al 2000, Lacy et al 2001, Adeoye et al 2009 waited for the symptoms to go away or contacted friends, relatives, local general practioner or hospital staff for advice (Wester et al 1999, Mackintosh et al 2012. As many as 24% to 54% of the patients do not seek help within one hour after symptom onset and many fail to seek help at all (Rosamond et al 1998, Wester et al 1999, Mosley et al 2007.…”
Section: The Emergency Telephone Call and Ems System Activationmentioning
confidence: 99%